Intense pulsed light therapy for the treatment of facial erythema and hypertrophic scar after phenol peeling - Naomi Carrara Matsuura; Cibele Toledo; Victoria Linhares Maia Santana; Denise Steiner; Nabila Scabine Pessotti (Sociedade Brasileira de Dermatologia (SBD), 2024)
Facial erythema after phenol peeling is one of the expected effects of the healing process and collagen formation. Intense Pulsed Light (IPL) therapy is one of the forms used as a treatment accelerating recovery, reducing redness, inflammation, and itching symptoms that may occur after peeling. IPLT can also be used to treat hypertrophic scars, which is also one of the adverse events that can happen with deep peeling. We report a successful case of IPLT treatment in a patient who presented facial erythema and hypertrophic scarring after undergoing phenol peeling.